Optimalisasi peran local wisdom dalam pengembangan minapolitan di Kabupaten Malang - Adhinda Dewi Agustine (Universitas Merdeka Malang, 2020)
Optimizing the role of local wisdom in Minapolitan development is a reference for the implementation of development programs. For this reason, it is necessary to disseminate it to the community, especially people who are actors of development in the marine and fisheries sector. Intensive communication based on the spirit of kinship and professionalism must continue to be developed so that the results of marine and fisheries development can be enjoyed more equitably and fairly by all people of Malang Regency. Empowerment of this minapolitan is the joint responsibility of the Government, educational institutions (especially universities), bank and non-bank financial institutions, as well as the community. The availability of large potential marine and fisheries natural resources, as well as adequate quality of human resources, and adequate existence Fisheries Service institution with adequate technology support in the field of fisheries is very important to strengthen the synergy of local wisdom in Malang Regency towards a more advanced and beneficial for the community. Optimization and financial contribution to regional income in Malang Regency can be a pilot strategy from other regions that have similar cases and phenomena. Keyword: optimization, local wisdom, minapolitan development